2012
DOI: 10.3141/2266-07
|View full text |Cite
|
Sign up to set email alerts
|

Fiber-Reinforced Asphalt Concrete as Sustainable Paving Material for Airfields

Abstract: Sustainability at airports has received attention recently as owners have worked to incorporate sustainable practices into projects and daily operations. Several guides have been published by airport agencies to document sustainable practices. One potential practice involves alternative paving materials for airfield pavements. Specifically, fiber-reinforced asphalt concrete has shown promising results and has recently been used to resurface Runway 1–19 at the Jackson Hole Airport in Jackson, Wyoming. This pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 5 publications
1
20
0
Order By: Relevance
“…Inclusion of fibers in the asphalt mixtures is gathering strength as they 101 act as a reinforcement, adding ductility and tensile strength to the material due to the enhanced 102 interlocking of aggregates. The interconnection between aggregates and fibers enables the material to withstand additional strain energy before cracking occurs; thereby, it is of great significance for extending the useful life of safer roads [28,35].…”
Section: Mechanical Characterization Of Fibersmentioning
confidence: 99%
“…Inclusion of fibers in the asphalt mixtures is gathering strength as they 101 act as a reinforcement, adding ductility and tensile strength to the material due to the enhanced 102 interlocking of aggregates. The interconnection between aggregates and fibers enables the material to withstand additional strain energy before cracking occurs; thereby, it is of great significance for extending the useful life of safer roads [28,35].…”
Section: Mechanical Characterization Of Fibersmentioning
confidence: 99%
“…Additionally, a research investigated a polyester fibre reinforced asphalt mix in accelerated loading facility with the results to show remarkably better fatigue cracking resistance for the reinforced section than that of the polymer-modified (Gibson et al, 2012). Similar study using the same type of synthetic fibres concentrated on comparing the result of three different mixes: the field samples with fibre (0.5 kg/ton) from Jackson Hole Airport, without fibre from Sheridan County Airport, and one lab-designed mix without fibre (Stempihar et al, 2012). Finally, it has been observed that the synthetic fibres started to absorb strain energy and to reduce the crack propagation when the crack began to propagate at intermediate and high temperatures (Muftah et al, 2017).…”
Section: Characteristics Of Synthetic Fibre Reinforced Asphaltic Matementioning
confidence: 96%
“…Over the years, various technologies have been proposed to improve the performance of asphalt pavements, and one of these is the utilisation of fibres as reinforcement in asphaltic materials (NCHRP Synthesis 475, 2015). Reinforcing with fibres, and mainly synthetic fibres have been used widely in asphalt pavements (Edgar, 1998;Gibson et al, 2012;Gibson & Li, 2015;Guistozzi, Crispino, Toraldo, & Mariani, 2015;Ho, Shan, Wang, Chen, & Almonnieay, 2016;Kaloush, Biligiri, Zeiada, Rodezno, & Reed, 2010;McDaniel & Shah, 2003;Muftah, Bahadori, Bayomy, & Kassem, 2017;Prowell, 2000;Stempihar, Souliman, & Kaloush, 2012) because of the capacity of synthetic fibre-reinforced systems to withstand additional strain energy before cracking and to add extra tensile strength to the material. In other words, these systems are able to retard the deterioration progress of pavements.…”
Section: Introductionmentioning
confidence: 99%
“…Fiber-reinforcement is recognized as for enhancing certain properties on hot mix asphalt (HMA); in particular, the addition of fibers influences the viscoelasticity of the mix and enhances dynamic modulus, reduces moisture susceptibility and rutting and improves fatigue resistance [30][31][32][33]. Limited research is available about fiber-reinforced cold mixtures.…”
Section: Fiber-reinforced Crmmentioning
confidence: 99%